Clinical and onychoscopic features of histopathologically proven onychopapillomas and literature update. (30th August 2021) - Starace, Michela; Alessandrini, Aurora; Ferrari, Tiziano; Wong, Vivian; Baraldi, Carlotta; Piraccini, Bianca Maria
Abstract: Background: Onychopapilloma is a benign tumor of the distal nail matrix and proximal nail bed with heterogeneous clinical presentations. It poses a diagnostic challenge because it could mimic subungual malignancies and inflammatory conditions. Clinical, onychoscopic, and histopathological clues play critical roles in diagnosis. Methods: We performed a retrospective chart review of onychopapilloma cases collected over 10 years, and characterized the clinical, onychoscopic, and histopathological features of onychopapilloma at an academic institution. Results: We obtained 17 biopsy‐confirmed cases of onychopapilloma. Among our cases, we found manifestation of onychopapilloma as longitudinal erythronychia, longitudinal leukonychia, yellow‐brown chromonychia, and longitudinal melanonychia. Long longitudinal or short splinter hemorrhages may be present. Distal fissuring with V‐shaped notch, subungual keratotic mass, and onycholysis are other discernable features. Histopathological features include papillomatosis, epidermal hyperplasia, acanthosis of the distal nail bed, premature keratinization, matrix metaplasia, hyperkeratosis, and splinter hemorrhages; histopathological signs of malignancy were not observed in any of our cases. Conclusions: Onychopapilloma has polymorphic clinical and morphological features. Onychoscopic and histopathological studies are important to help exclude malignant mimickers. Consider onychopapilloma in the differential diagnoses of a monodactylous longitudinal streak in the nail, especially on the left thumb of an adult female.